A Longitudinal Study of Nursing Staffs’ Shift Schedules during the COVID-19 Pandemic - Isabelle Hernandez; Ann Rudman; Philip Tucker; Göran Kecklund; Anna Dahlgren (Nordic Journal of Working Life Studies)
Working conditions among healthcare workers became more demanding during the COVID-19 pandemic, and new types of work hour schedules emerged. The aim of the study was to investigate how working hours in the Swedish healthcare sector were affected by the COVID-19 pandemic. Payroll data were extracted from one mid-size Swedish region, including 1,130,391 shifts worked by 3392 individuals between December 2018 and September 2023. Paired t-tests were used to compare working hours before and after the onset of COVID-19. There were few changes to the working hours during COVID-19. A new schedule (4 workdays, 2 days off) increased weekend work and decreased the proportion of quick returns and single free days. Exploratory analyses showed that overtime increased. In conclusion, the pandemic had few and weak effects on the ergonomic qualities of work hour schedules. More research is needed to explore whether the findings are representative of other contexts.